Reviewing Transition Economies (1989-2021): Sustainable Reform Outcomes in Post-Socialist Countries - Boguslavskyi, Oleksandr; Gura, Viktoriya; Nikitina, Tatyana (My University, 2025)
Стаття присвячена оцінці результатів реформ у перехідних економіках за 1989-2021 роки за допомогою кластерного аналізу. У статті виділено 27 індикаторів, що характеризують основні параметри трансформацій 25 постсоціалістичних країн ЦСЄ, Південно-Східної Європи, Балтії, Південно-Східної Азії, колишніх країн СНД тощо. За допомогою методів ліктьового, силуетного та геп-аналізу визначено оптимальну кількість кластерів для країн з перехідною економікою. Метод Уорда був використаний для кластеризації країн з перехідною економікою на дві групи та для створення діаграми з межами кластерів. До першої групи належать країни, які менш успішні у реформуванні, до другої – країни, які досягли значних результатів у реформуванні. На основі аналізу зроблені висновки та рекомендації щодо розвитку соціального підприємництва як рушійної сили поширення соціальних інновацій.
The article is devoted to the assessment of the results of reforms in transition economies for 1989- 2021 using cluster analysis. The article allocates 27 indicators characterizing the main parameters of the transformations of 25 post-socialist countries of CEE, SEE, Baltic, South East Asia, former CIS countries, etc. Using the methods of elbow, silhouette and gap analysis, the optimal number of clusters for transition countries is determined. The Ward method was used to cluster the transition countries into two groups and to draw a diagram with the boundaries of the clusters. The first group includes countries that are less successful in reforming, and the second group includes countries that have achieved significant results in reforming. Based on the analysis, conclusions and recommendations are drawn towards social entrepreneurship development as a driving force of social innovative dissemination.
Keywords: кафедра готельно-ресторанної справи; кластерний аналіз; перехідна економіка; cluster analysis; transition economies; public administration